2016
DOI: 10.17811/ebl.5.4.2016.107-112
|View full text |Cite
|
Sign up to set email alerts
|

The impact of supply shocks on unemployment in Spain

Abstract: In this paper we aim to investigate how the relationships of falls and rises in the oil price with the unemployment rate and the equilibrium unemployment rate differ in the case of Spain. It is found that while oil price movements do not have an effect on unemployment, they do have a differential effect on the equilibrium rate of unemployment for our target country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
1
0
2
Order By: Relevance
“…With respect to unemployment dynamics and oil prices 3 , Andreopoulos (2009), Caporale and Gil-Alana (2002), Gil-Alana (2003, 2006 and Kartircioglu et al (2015) find that the oil price is negatively related to unemployment. Using nonlinear models, Andreopoulos (2009) and Cuestas (2016) find that it is important to distinguish between positive and negative oil price shocks when studying the relationship between oil prices and unemployment as there is evidence of asymmetric effects. More recently, Cuestas and Ordóñez (2018) analyse the link between UK unemployment and oil price movements using Bayesian SVAR (BSVAR) methods, and find that the relationship between these two variable differ before and after 2008.…”
Section: Brief Literature Review and Frameworkmentioning
confidence: 99%
“…With respect to unemployment dynamics and oil prices 3 , Andreopoulos (2009), Caporale and Gil-Alana (2002), Gil-Alana (2003, 2006 and Kartircioglu et al (2015) find that the oil price is negatively related to unemployment. Using nonlinear models, Andreopoulos (2009) and Cuestas (2016) find that it is important to distinguish between positive and negative oil price shocks when studying the relationship between oil prices and unemployment as there is evidence of asymmetric effects. More recently, Cuestas and Ordóñez (2018) analyse the link between UK unemployment and oil price movements using Bayesian SVAR (BSVAR) methods, and find that the relationship between these two variable differ before and after 2008.…”
Section: Brief Literature Review and Frameworkmentioning
confidence: 99%
“…Analiz sonuçlarında petrol fiyatlarındaki pozitif şokların üretim düzeyini azalttığı, negatif şokların ise artırdığı tespit edilmiştir. Cuestas (2016), İspanya ekonomisi için 1997: M12-2016: M4 döneminde petrol fiyatları ile işsizlik arasındaki asimetrik ilişkiyi NARDL yöntemi ile araştırmış, analiz sonuçlarında petrol fiyatlarının işsizliği etkilemediği ancak petrol fiyatlarındaki pozitif şokların doğal işsizlik oranını artırdığını tespit etmiştir. Yung ve Das ( 2018) çalışmalarında ABD ve Kanada ekonomileri için petrol fiyatları ile işsizlik arasındaki asimetrik nedensellik ilişkisini araştırmışlardır.…”
Section: Li̇teratürunclassified
“…In their two contributions, Jiménez-Rodríguez 2009and Jiménez-Rodríguez and Sánchez (2005) find that in most cases only positive innovations have an effect on growth, although again there are some differences depending on the countries considered. Andreopoulos (2009), Cuestas (2016) and Gil-Alana (2003, 2006 find that oil price shocks tend to have negative effects on employment and that there is evidence that the effects of positive and negative shocks may differ in magnitude. These results are in line with the theoretical foundations of Hamilton (1983Hamilton ( , 1988 and Carruth et al (1998), according to which an oil price shock can be identified as an aggregate supply shock, in particular in net oil importing countries such as the UK.…”
mentioning
confidence: 99%